Implementasi Metode Statistical Quality Control (SQC) dalam Pengendalian Mutu Beton pada Proyek Konstruksi - Abi, Faza Ardisa Sabian Alathas; Mocahmmad Safrizala Al Farizi; Ahmad Rijal Zufri; Widarto Sutrisno; Detha Sekar Langit Wahyu Gutama (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Concrete is widely used in the construction of buildings, bridges, and roads. The quality of concrete affects the stability and durability of the structure, so quality control in concrete production is very important. One of the methods that can be applied in concrete quality control is Statistical Quality Control (SQC). This study aims to test the quality of concrete through fine and coarse aggregate testing, specific gravity testing, water absorption, bulk specific gravity, sludge content, job mix test, and concrete bending strength test. The test results showed that the resulting concrete had a bending strength higher than the required standard, which was an average of 48.04 kg/m² which was greater than 45 kg/cm². These results show that the FS 45 concrete tested has quality that meets the criteria and can be applied to construction with good performance.